Enhanced mineralization of oxalate by highly active and Stable Ce(III)-Doped g-C3N4 catalyzed ozonation. (January 2020) - Xie, Yu; Peng, Shuhan; Feng, Yong; Wu, Deli
Abstract: The degradation of carboxylic acid has been identified as one of the rate-determining steps in the mineralization of organic pollutants by ozonation. In this study, Ce(III)-doped graphitic carbon nitride (Ce–CN) composites with different Ce(III) contents were synthesized and used as catalysts for the ozonation of oxalate. The morphology and structure of the Ce–CN were comprehensively characterized using various techniques such as SEM, XRD, FTIR, and XPS. The results show that the structure of g-C3 N4 provided an ideal site for the accommodation of Ce(III) and thus facilitated the formation of surface hydroxyl groups. With 2.5%Ce–CN as a catalyst, the degradation efficiency of oxalate was increased by 47.1% after reaction for 30 min. The decomposition of ozone was accelerated in the presence of Ce–CN. Hydroxyl radicals were recorded by electron spin resonance and identified as the major actives species. Under the catalysis of 2.5%Ce–CN, the production of hydroxyl radicals was increased by 40%. The Ce(III) and surface hydroxyl groups that distributed uniformly on the surface of Ce–CN were speculated as the dual catalytic sites for the complexation of oxalate and activation of ozone, respectively. Ce–CN had a high stability and reutilization capability. It is proposed that a complex was formed between surface Ce(III) and oxalate, and this complex could be more easily attacked by the surrounding ozone and hydroxyl radicals than free oxalate. As oxalate is a typical recalcitrant carboxylic acid, the findings from this study are expected to promote the application of ozonation in the removal of organic pollutants. Graphical abstract: Image 1 Highlights: Dual reaction sites of Ce(III)/≡OH on g-C3 N4 was used for catalytic ozonation. Stable Ce(III) doping was realized by g-C3 N4 coordination and ≡OH formation. Complexation between ≡Ce(III) and OA is crucial step for enhanced mineralization.